Government Social Responsibility: Its Essense And Forms; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 38 : Lifelong Wellbeing in the World (WELLSO 2017) - Rudneva E. L. (2018, 2018)
Title screen